Participação do terceiro setor na execução de políticas públicas: o caso do município de Itapeva - Camargo, Maria Emília Silveira (2018)
This research presents a theoretical-conceptual approach regarding the participation of the Third Sector in the achievement of public policies in the Municipality of Itapeva / SP. Starting from the study of the concept of the Third Sector and its implementation in Brazil during the Reform of the State Apparatus proposed in the Fernando Henrique Cardoso Government in 1995, with the publication of the Master Plan for State Reform, it was sought to understand the evolution of the Publicization of non-exclusive activities of the State, reaching the model proposed by the Regulatory Framework of Civil Society Organizations - Federal Law 13,019, dated July 31, 2014. In the light of such concepts, research was carried out on the participation of the Third Sector in the execution of public policies in the Municipality of Itapeva / SP, investigating how the participation of the Third Sector in the execution of public policies in the locality has occurred, it is understood how social organizations are involved in the achievement of public policies, according to the adjustments made in the period from 2014 to 2018. As a result of the research, the concentration of activities in the areas of education, health and social assistance, the amounts invested per area and the deficiencies and limitations in the follow-up of the adjustments, as to the quality and efficiency of the services.